(untitled) (Bangladesh Journal of Medical Science, 2024)
The current study is aimed at evaluation of the impact of different surgical approaches while correcting congenital heart diseases (CHD). Clinical outcomes like; operative time, complications, hospital stay were evaluated in children undergoing surgical repair of atrial septal defect (ASD) and ventricular septal defect (VSD). Patients and methods: Between 2015 and 2019, a total of 111 patients surgically managed for CHD with male: female ratio of…. and mean age 10.42±3.24 years. Two surgical approaches: open either right anterolateral thoracotomy or sternotomy and thoracoscopic were used. The study conducted to determine the operative time, ICU stay, complications, recovery period and long term follow up of the patients in both the groups. Results: 67 patients with ASD and 44 patients with VSD underwent cardiac surgery. Mean operation time was significantly longer in TS patients in comparison with TT and ST groups. However, mean intensive care unit (ICU) stay and hospital stay were significantly shorter in TS group in comparison with TT and ST patients. Conclusion: TS approach in repair of congenital heart defects not only resulted of good cosmetic effect, but also reduces time in ICU and hospital stay in comparison with “classical” operational techniques. In this article we tried to show the whole results of research. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 115-120